Rancang Bangun Alat Sortir Otomatis Buah Apel Dan Buah Jeruk Berbasis Arduino Uno 328 - Brian Adams Laia; Agus Almi Nasution; Ahmad Yanie (JOURNAL OF ELECTRICAL AND SYSTEM CONTROL ENGINEERING, 2025)
The average livelihood in Indonesia is farming, with Agriculture Minister Limpo stating an increase of 8 million farmers during the Covid-19 pandemic. Although economic activity has decreased, the agricultural sector has experienced a significant increase, especially plantation commodities as a contributor to the country's foreign exchange. In this context, the process of sorting fruits such as apples and oranges is important to determine classification based on quality. The design of an automatic sorting tool uses Arduino Uno 328 as a processor of input signals from proximity sensors, color sensors, and ultrasonic sensors. The proximity sensor detects the presence of fruit, while the color sensor identifies the color, and the ultrasonic sensor distinguishes the size. The output is displayed on the LCD, which shows data on the size and color of the fruit. The working principle of this tool is that the proximity sensor detects the presence of fruit entering the conveyor, with data sent to the Arduino and displayed on the LCD. The color and ultrasonic sensors also send relevant information. The servo motor drives the conveyor, directing the fruit to the place according to size. Test results show that the proximity sensor functions effectively at a distance of 1-5 cm, while the ultrasonic sensor shows a range of 3.2-10.4 cm, and the power consumption of the tool reaches 120 watts.